Determinants of tobacco use during pregnancy and pregnancy surveillance - Emília Coutinho; Carlos Pereira; Paula Nelas; Claudia Chaves; Odete Amaral; Carla Cruz (INFAD, 2018)
A non-smoking pregnancy translates into more health for the mother and the child. Pregnancy surveillance ensures the timely identification of risk factors and the possibility of early prenatal care that prevents complications. The nurse assumes himself as a professional in promoting health and preventing complications in the follow-up of the woman / couple throughout pregnancy and in the awareness of the importance of adopting healthy lifestyles. Objective: Identify the determinants of tobacco use and pregnancy surveillance. Methodology: This is a quantitative, cross-sectional, descriptive and correlational study with a sample of 3232 mothers. The study was carried out in 32 maternity / maternity hospitals, from north to south of Portugal, in the obstetrics / inpatient postpartum service between 2010 and 2012. The data collection instrument was the questionnaire that allowed the sociodemographic characterization of the sample with a mean age of women of 28.75 years (SD = 5.463 years), 78.2% Portuguese and 21.8% foreign. Ethical procedures were ensured and the study was authorized by the National Data Protection Commission in addition to the favorable opinions of the ethics committees of the institutions involved. The data was processed with the SPSS program (Statistical Package for the Social Sciences) version 24 for Windows. Results: A woman who lives with a partner who has not planned pregnancy is more likely to have adequate pregnancy surveillance and not consume tobacco during pregnancy. On the other hand, a woman living in a rural area, with a higher vocational training or technical training, who is not employed, has had health problems during pregnancy and has not been prepared for childbirth, is less likely to surveillance her pregnancy and more likely to be a tobacco user. Conclusion: Adequate pregnancy surveillance ensures the timely identification of risk factors such as tobacco use and the possibility of timely sensitization of the woman / couple to a non-smoking pregnancy and for the prevention of complications.